Informatorzy, tłumacze i obserwatorzy: zbieranie (meta)danych i wdrażanie badań w cyfrowej ponowoczesności. W stronę metod opartych na współpracy - Ogonowska, Agnieszka (Załącznik Kulturoznawczy, 2024)
Contemporary media studies are opening up to methods developed in social sciences, which results from the dynamic development of the mediasphere, the attributes of new digital media and the (network) activities of their users. The latter, within the framework of collaborative media anthropology, actively participate in all phases of the research project, which, on the one hand, makes them inclusive and, on the other hand, imposes new ethical and methodological obligations on the academic researcher. This approach is a specific materialization of Margaret Mead’s idea related to the transfer of knowledge and learning strategies in prefigurative societies, in the 21st century from digital natives, and refers to the collaborative ethnography of Luc Eric Lassiter. New ideas and challenges in applied media studies, collaborative research models and related methodological “transgressions” are also important in changing the philosophy of thinking regarding the obligations of media studies and rules of media literacy 4.0.